2021
DOI: 10.1063/5.0046870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slope and speed of escalator on the dispersion of cough-generated droplets from a passenger

Abstract: During the pandemic of COVID-19, the public is encouraged to take stairs or escalators instead of elevators. However, the dispersion of respiratory droplets in these places, featured by slopes and human motion, is not well understood yet. It is consequently unclear whether the commonly recommended social-distancing guidelines are still appropriate in these scenarios. In this work, we analyze the dispersion of cough-generated droplets from a passenger riding an escalator with numerical simulations, focusing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“… Xu and Chraibi (2020) Micro Simulation Ronchi and Lovreglio (2020) Discrete Event Simulation Kierzkowski and Kisiel (2020) ; Ridenhour et al (2011) ; Swinarski (2020) Cellular Automata Monte Carlo Simulation Dabachine et al (2020) ; Larson and Nigmatulina (2010) ; F. Liu et al (2021) System Dynamics Lant et al (2008) Particle Propagation Model Kudryashova et al (2021) Computational Fluid Dynamics Leng et al (2020) ; Miller et al (2020) ; Satheesan et al (2020) ; C. Sun and Zhai (2020) ; Yu et al (2017) ; Domino (2021) ; H. Li et al (2021) ; Yamakawa et al (2021) ; Komperda et al (2021) ; Z. Li et al (2021) ; Sen and Singh (2021) ; Lim et al (2011) ; Y. Li et al (2005) ; Gao et al (2008) Building Information Modelling Pavon et al (2020) Transient Systems Simulation Balocco and Leoncini (2020) Statistical Model Applied Probability Model Kaplan (2020) ; Tupper et al (2020) Linear Regression Cartenì et al (2021) ; Hong et al (2021) Multilevel Linear Modelling Hamidi and Zandiatashbar (2021) Logistic Regression Spencer et al (2020) Negative Binomial Regression ...…”
Section: Resultsmentioning
confidence: 99%
“… Xu and Chraibi (2020) Micro Simulation Ronchi and Lovreglio (2020) Discrete Event Simulation Kierzkowski and Kisiel (2020) ; Ridenhour et al (2011) ; Swinarski (2020) Cellular Automata Monte Carlo Simulation Dabachine et al (2020) ; Larson and Nigmatulina (2010) ; F. Liu et al (2021) System Dynamics Lant et al (2008) Particle Propagation Model Kudryashova et al (2021) Computational Fluid Dynamics Leng et al (2020) ; Miller et al (2020) ; Satheesan et al (2020) ; C. Sun and Zhai (2020) ; Yu et al (2017) ; Domino (2021) ; H. Li et al (2021) ; Yamakawa et al (2021) ; Komperda et al (2021) ; Z. Li et al (2021) ; Sen and Singh (2021) ; Lim et al (2011) ; Y. Li et al (2005) ; Gao et al (2008) Building Information Modelling Pavon et al (2020) Transient Systems Simulation Balocco and Leoncini (2020) Statistical Model Applied Probability Model Kaplan (2020) ; Tupper et al (2020) Linear Regression Cartenì et al (2021) ; Hong et al (2021) Multilevel Linear Modelling Hamidi and Zandiatashbar (2021) Logistic Regression Spencer et al (2020) Negative Binomial Regression ...…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al104 investigated airborne particle exposure in elevators. Li et al105 used theLagrangian method to evaluate the impact of the speed, slope, and direction of an escalator on the spread of droplets. All these studies indicated that the Lagrangian model could be used to assess the risk of exposure to airborne particles.The Eulerian and Lagrangian models are usually coupled with numerical calculations of the flow field.…”
mentioning
confidence: 99%
“…Also, only a single passenger was included for risk evaluation of infectious droplets and the interaction with other passengers was ignored in the previous studies. 20,21 In this paper, we investigate the effect of cough-generated droplets expelled from an infected person on other passengers riding the same escalator. A geometrically detailed escalator model is used with steps and handrails moving in ascending and descending directions.…”
Section: Practical Implicationmentioning
confidence: 99%